A Mathematical Model of Black Rhino Translocation Strategy - Dipo Aldila; Ashleigh Jane Hutchinson; Matthew Woolway; Norman Owen-Smith; Edy Soewono (Institute for Research and Community Services (LPPM) ITB, 2015)
A deterministic mathematical model of the black rhino population in South Africa will be discussed. The model is constructed by dividing the black rhino population into multiple patches. The impact of human intervention on different translocation strategies is incorporated into the model. It is shown that, when implemented correctly, translocation can accelerate the growth rate of the total black rhino population. Equilibrium points are shown with their local stability criteria.